Writing multi-discursive ethnography as critical discourse study: the case of the Wenchang Palace in Quzhou, China. Issue 1 (1st January 2017) - Hou, Song; Wu, Zongjie
ABSTRACT: This paper proposes to use 'multi-discursive ethnography' to move critical discourse analysis/studies beyond an analytical enterprise so that it may transcend the 'critical/positive' dichotomy and the language dilemma researchers confront. As an alternative form of critical discourse study, multi-discursive ethnography seeks to explore different discourses of a subject matter and weave them together for dialogue and diversity. As such, it not only challenges dominant discursive construction of the subject matter at stake, but also endorses corresponding local, cultural ways of speaking and thinking. Using the Wenchang Palace in a transdisciplinary project at a historical neighborhood in Quzhou, China, as the case, the paper illustrates how a multi-discursive ethnography of this no longer materially existing heritage site is written to facilitate critiquing of the 'authorized heritage discourse' from the West and simultaneously promote pertinent local voices and deep-rooted cultural language for multi-discursive dialogue.